PENERAPAN SISTEM COMPUTER ASSISTED TEST (CAT) DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI KEMENTERIAN KEUANGAN REPUBLIK INDONESIA - Yuliandri, Randi; Erowati, Dewi (Journal of Politic and Government Studies, 2019)
Corruption is still rampant in Indonesia, one of the acts of corruption committed by certain persons are in the field of civil service, which is currently in the recruitment and selection of Indonesian civil servant. Therefore, the government made a bureaucratic reform in the field of personnel. CAT system is present to change the old recruitment system manually into a computer-based system. This study examines the computer assisted test system at the Ministry of Finance of the Republic of Indonesia in producing high quality human resources to realize a good governance in Indonesia. The method used is descriptive qualitative approach to data collection techniques are observation, interviews and document research. Informants in this study is the Head of Planning and Procurement Human Resources, Ministry of Finance, Head of the Division of Recruitment and Selection of Human Resources, Ministry of Finance, Head of the Division of Planning and Formation of Human Resources, Ministry of Finance, Head of Subdivision Placement Human Resources, Ministry of Finance, Head of Management of information technology Selection State Personnel Board, Chief PLT section Recruitment CPNS Ministry for Administrative and Bureaucratic Reform, ASN who pass in the Ministry of Finance in 2017, and employess who were not selected in the Ministry of Finance in 2017. The results showed that the CAT system is able to provide transparency and objectivity well. This had a positive impact in order to avoid the practices of corruption committed by certain elements. The use of a threshold value at the time of selection get SDM with good integrity. At the Ministry of Finance, HR produced has the responsiveness and alertness of the good, as evidenced by the achievements of the Ministry of Finance's risk management performance in 2018 had a rate of 120 percent, an increase compared with 2017 which only has a value of 100 percent is done by employees of non-CAT. This system successfully make changes to governance in the field of personnel.Keywords: Ministry of Finance, CAT Systems, Human Resources